(3EYLGR GdbQBfs - (3eMeO Hf GdWjH Hf eMeO Hf LYaQ, Jbj GdOjf CHh HcQ, GdbGVj GdHGbdGfj , J (B403 (3g` s
(3ChdgG (B:s
(3jHJOF CKfGA GdebOeI HbhdI (B( (3hef Cge eG jLH Ydi Cgd Ojf Gddg cTag hChdi eG jdRe HMKg eG cGf dCUd Ojfge bhGekG hJbGYOg s
(3BNQgG (B:s
(3HGH GdHMK heNjd GdEdg ai hLg GdaMU hgh MSHi hMSHc hfYe Gdhcjd hGdMeO ddg QH GdYGdejf s
(3fSNI faSjI LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B120s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds